Answer:
Explanation:
Simplifying
4(t + 1) = 6(g + -4)
Reorder the terms:
4(1 + t) = 6(g + -4)
(1 * 4 + t * 4) = 6(g + -4)
(4 + 4t) = 6(g + -4)
Reorder the terms:
4 + 4t = 6(-4 + g)
4 + 4t = (-4 * 6 + g * 6)
4 + 4t = (-24 + 6g)
Solving
4 + 4t = -24 + 6g
Solving for variable 't'.
Move all terms containing t to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + 4t = -24 + -4 + 6g
Combine like terms: 4 + -4 = 0
0 + 4t = -24 + -4 + 6g
4t = -24 + -4 + 6g
Combine like terms: -24 + -4 = -28
4t = -28 + 6g
Divide each side by '4'.
t = -7 + 1.5g
Simplifying
t = -7 + 1.5g